A Longitudinal Study of Gun Violence Attitudes: Role of Childhood Aggression and Exposure to Violence, and Early Adolescent Bullying Perpetration and Victimization. (2nd January 2020) - Nickerson, Amanda B.; Shisler, Shannon; Eiden, Rina D.; Ostrov, Jamie M.; Schuetze, Pamela; Godleski, Stephanie A.; Delmerico, Alan M.
ABSTRACT: This prospective study examined the effects of early childhood physical aggression and violence exposure on bullying victimization/perpetration and attitudes toward guns and violence in early adolescence (EA) in a high-risk sample. Participants included 216 mother–child dyads from an ongoing longitudinal study using multi-method assessments (e.g., classroom observations; laboratory assessment; parent, teacher, and child self-reports). Results supported a developmental pathway from early adversity (i.e., prenatal substance use) to aggression at kindergarten age to bullying perpetration and gun violence attitudes (aggressive responses to shame) in EA. Higher peer victimization was also associated with aggressive responses to shame in EA. Results are discussed in light of the complexity of the motives for aggression and the need for prevention and early intervention.